Successful transurethral endoscopic removal of a toothpick embedded in the bladder wall: a rare Case Report - Ma, Tao; Guo, Jianjun; Cao, Guihua; Cai, Qian; Yu, Yin; Zhou, Lijun (Frontiers in Surgery, 2025)
BackgroundThis report describes a rare case of a wooden toothpick embedded in the bladder muscular layer and shares the experience of successful diagnosis and treatment.Case presentationA 29-year-old female patient with a history of cesarean section was admitted due to persistent lower abdominal pain and dysuria lasting one month. Preoperative three-dimensional CT imaging was performed, using a crucian carp with an inserted injection needle as a density reference. Density comparisons between the foreign body, needle, and fishbone suggested that the foreign body was unlikely a retained needle or fishbone. Considering the patient's dietary habits, it was suspected that the object was an accidentally swallowed wooden toothpick. The patient underwent ultrasound-guided transurethral surgery, during which a wooden toothpick approximately 3.4 cm long, 4 mm wide at its midsection, with a rough surface, was successfully removed. Postoperative imaging confirmed the complete removal of the foreign body, and the patient recovered well. During a six-month follow-up, the patient reported no urinary or abdominal symptoms.ConclusionA detailed patient history and imaging studies are crucial for diagnosing unexplained bladder foreign bodies. Ultrasound-guided transurethral cystoscopic surgery is an effective method for removing bladder foreign bodies. This case provides valuable insights for managing and treating similar complex cases.